Investigation of adverse effects of oral voriconazole in the treatment of fungal infection using The FDA Adverse Event Reporting System (FAERS) - Onanna, Kazi (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.